Performance Testing of Centrifugal Pump Type with 3 Hp Power - Wasiran Wasiran; Waluyo Djoko Yudisworo; Endang Prihastuty (Mestro, 2022)
Pumps are fluid machines whose uses are very broad and important, ranging from industry to household needs. Selection of pump performance characteristics is very important and must be adjusted to the needs which include: discharge, head, power, and rotation. The performance characteristics of the pump are obtained through testing. In connection with the importance of information about pump performance characteristics, through this research activity efforts will be made to test centrifugal pumps using 3 hp of power. In this research, the data obtained from the direct test results will be entered, where the test is carried out at the Machine Performance Test Laboratory. In this test, the pump pressure data obtained from the gauge gradually with several valve openings, then the data is entered into the data table that has been prepared. The test was carried out to test the ability of the centrifugal pump test equipment using 3 HP power which was prepared as one of the laboratory pump test equipment for engine performance testing. In testing the centrifugal pump there are 3 variables that will be used to carry out the test, namely the first by using a tachometer which is useful for measuring shaft rotation, the second by using a Bordoun manometer which is useful for measuring fluid pressure, the third by using an orifice which functions to measure speed fluid.